Basic researchChronic alcohol exposure increases ganglia endogenous morphine levels - Zhu, Wei; Li, Yiqing; Kream, Richard M.; Stefano, George B. (Archives of Medical Science, 2010)
Introduction: We have previously demonstrated that alcohol has the ability to release low levels of endogenously expressed, chemically authentic, morphine from neural tissues. Material and methods: Presently, we demonstrate that chronic exposure of Mytilus edulis pedal ganglia tissues maintained in organotypic culture to very concentrations of 1 mM and 10 mM ethanol induces a time dependent increase in both endogenous morphine and dopamine (DA) levels. Results: Chronic incubation of M. edulis pedal ganglia with 3 concentrations of DA resulted in statistically significant elevations of cellular morphine levels, thereby confirming previous studies from our laboratory establishing DA as an essential precursor in the morphine biosynthetic pathway. Conclusions: By understanding multiple debilitating effects of alcohol on “morphinergic” signaling, we may understand the ravages of neural processes associated with alcohol abuse and how its treatment may be made more effective.